2020
DOI: 10.1212/wnl.0000000000009982
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following diagnosis of low-grade glioma

Abstract: Objective:Return-to-work (RTW) following diagnosis of infiltrative low-grade gliomas (LGG) is unknown.Methods:Swedish patients with histopathological verified WHO grade II diffuse glioma diagnosed between 2005-2015 were included. Data were acquired from several Swedish registries. A total of 381 patients aged 18-60 were eligible. A matched control population (n=1900) was acquired. Individual data on sick leave, compensations, comorbidity and treatments assigned were assessed. Predictors were explored using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Of the remaining 242 patients, we excluded another 36 patients from the subpopulation that were not on registered sick leave on the day of surgery. As described previously [ 32 , 42 ], this indicated that those patients were detached from the Swedish sick leave system and did not consistently receive compensation for sick leave. The remaining 206 patients constituted the return to work cohort (RTW cohort).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Of the remaining 242 patients, we excluded another 36 patients from the subpopulation that were not on registered sick leave on the day of surgery. As described previously [ 32 , 42 ], this indicated that those patients were detached from the Swedish sick leave system and did not consistently receive compensation for sick leave. The remaining 206 patients constituted the return to work cohort (RTW cohort).…”
Section: Methodsmentioning
confidence: 77%
“…The linkage of SBTR to other national registries has been described in our previous studies [ 32 , 42 ]. In short, SBTR is a nationwide, but regionally based, registry of adult (≥ 18 years) patients with primary brain tumors, with a surgically acquired histopathological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…We did not compare our patient cohort to other tumor or spinal-trauma entities, as we only included patients undergoing spinal ependymoma surgery. While occupational reintegration data has been described for intracranial glioma patients 27 , 28 and a small group of spinal ependymoma patients 13 , there is no evidence on sport activities and recreation in primary spinal cord tumor patients. Comparable available studies mostly included patients suffering from spinal cord injuries, with considerably worse neurological and clinical function and more possibilities for systematic reintegration and support programs 15 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…With the increased survival rate of the, usually young, adults diagnosed with low-grade glioma, employment status is a highly relevant topic. Earlier studies reported RTW rates between 54% and 70.7% in a variety of patients with glioma with a mean follow-up time of 1–4 years after diagnosis ( 10 , 24 , 25 ). A possible explanation as to why the RTW rate in the current study is at the low end of this range is the longer time post-diagnosis, with patients often developing progressive cognitive deficits over time, and the fact that patients were at risk of tumour progression for longer and needed re-treatment (re-resection, chemotherapy of radiotherapy) or neuro-deterioration ( 26 ).…”
Section: Discussionmentioning
confidence: 99%